2008
DOI: 10.1002/mus.20941
|View full text |Cite
|
Sign up to set email alerts
|

Atypical facet of Möbius syndrome: Association with facioscapulohumeral muscular dystrophy

Abstract: We describe a patient with facioscapulohumeral muscular dystrophy (FSHD) associated with Möbius syndrome and congenital ophthalmoplegia. This 7-year-old girl had profound limitation of extraocular movements since birth, congenital facial diplegia, neonatal hypotonia, and progressive limb-girdle weakness. FSHD genetic testing revealed a pathogenic haplotype with a D4Z4 repeat of 30 kb. The father carries the same allele, although is minimally affected. This unusual case expands the genotypic-phenotypic spectrum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 12 publications
(28 reference statements)
0
7
0
Order By: Relevance
“…Of note, standard deviations and interquartile ranges are indicative of substantial clinical variation that is characteristic of FSHD. Also, these severity scores have not been validated in early onset [26] 1982 USA Case-series 2 2 iFSHD + retinopathy Wulff [27] 1982 USA Case-report 1 1 iFSHD McGarry [28] 1983 USA Case-report 2 2 iFSHD Meyerson [29] 1984 USA Case-report 2 3 iFSHD + hearing loss Gieron [30] 1985 USA Case-report 3 4 iFSHD Gurwin [31] 1985 GBR Case-report 3 4 iFSHD Korf [32] 1985 USA Case-series 6 6 iFSHD + hearing loss Bailey [33] 1986 USA Case-report 1 8 iFSHD Voit [34] 1986 DEU Case-series 7 10 iFSHD + hearing loss Yasukochi [35] 1988 JPN Case-series 2 2 iFSHD + retinopathy Shapiro [36] 1991 USA Case-series 9 9 iFSHD Kamata [37] 1993 JPN Case-report 1 1 iFSHD Brouwer [13]* 1994 NLD Case-series 6 6 iFSHD † Jardine [38] 1994 GBR/DEU Case-series 19 27 iFSHD † Brouwer [21]* 1995 NLD Case-series 4 4 iFSHD Je Hyeon [39] 1995 JPN Case-report 1 1 iFSHD † Nakagawa [40] 1996 JPN Case-report 1 2 iFSHD † Nakagawa [40] 1997 JPN Population cohort 7 42 FSHD † Okinaga [41] 1997 JPN Case-series 2 3 iFSHD † Funakoshi [15] 1998 JPN Population cohort 20 127 FSHD ‡ Miura [42] 1998 JPN Case-series 2 2 iFSHD † Lapena [43] 2001 AUS Case-series 1 1 Vocal cord paralysis ‡ Dorobek [44] 2004 POL Case-report 1 2 iFSHD ‡ Wohlgemuth [45] 2004 NLD Case-series 4 10 FSHD + assisted ventilation ‡ Felice [46] 2005 USA Case-report 2 3 iFSHD ‡ Bindoff [47] 2006 NOR Case-series 2 2 iFSHD ‡ Klinge [16] 2006 GBR Case-series 7 7 iFSHD ‡ Saito [48] 2007 JPN Case-report 1 1 iFSHD Shields [49] 2007 USA Case-report 1 1 iFSHD ‡ Kolski [50] 2008 CAN Case-report 1 1 iFSHD ‡ Kriswalsky [51] 2008 USA Case-report 1 1 iFSHD ‡ Trevisan [17] 2008 ITA Case-series 5 7 iFSHD + 10-13Kb ‡ Lee…”
Section: Discussionmentioning
confidence: 99%
“…Of note, standard deviations and interquartile ranges are indicative of substantial clinical variation that is characteristic of FSHD. Also, these severity scores have not been validated in early onset [26] 1982 USA Case-series 2 2 iFSHD + retinopathy Wulff [27] 1982 USA Case-report 1 1 iFSHD McGarry [28] 1983 USA Case-report 2 2 iFSHD Meyerson [29] 1984 USA Case-report 2 3 iFSHD + hearing loss Gieron [30] 1985 USA Case-report 3 4 iFSHD Gurwin [31] 1985 GBR Case-report 3 4 iFSHD Korf [32] 1985 USA Case-series 6 6 iFSHD + hearing loss Bailey [33] 1986 USA Case-report 1 8 iFSHD Voit [34] 1986 DEU Case-series 7 10 iFSHD + hearing loss Yasukochi [35] 1988 JPN Case-series 2 2 iFSHD + retinopathy Shapiro [36] 1991 USA Case-series 9 9 iFSHD Kamata [37] 1993 JPN Case-report 1 1 iFSHD Brouwer [13]* 1994 NLD Case-series 6 6 iFSHD † Jardine [38] 1994 GBR/DEU Case-series 19 27 iFSHD † Brouwer [21]* 1995 NLD Case-series 4 4 iFSHD Je Hyeon [39] 1995 JPN Case-report 1 1 iFSHD † Nakagawa [40] 1996 JPN Case-report 1 2 iFSHD † Nakagawa [40] 1997 JPN Population cohort 7 42 FSHD † Okinaga [41] 1997 JPN Case-series 2 3 iFSHD † Funakoshi [15] 1998 JPN Population cohort 20 127 FSHD ‡ Miura [42] 1998 JPN Case-series 2 2 iFSHD † Lapena [43] 2001 AUS Case-series 1 1 Vocal cord paralysis ‡ Dorobek [44] 2004 POL Case-report 1 2 iFSHD ‡ Wohlgemuth [45] 2004 NLD Case-series 4 10 FSHD + assisted ventilation ‡ Felice [46] 2005 USA Case-report 2 3 iFSHD ‡ Bindoff [47] 2006 NOR Case-series 2 2 iFSHD ‡ Klinge [16] 2006 GBR Case-series 7 7 iFSHD ‡ Saito [48] 2007 JPN Case-report 1 1 iFSHD Shields [49] 2007 USA Case-report 1 1 iFSHD ‡ Kolski [50] 2008 CAN Case-report 1 1 iFSHD ‡ Kriswalsky [51] 2008 USA Case-report 1 1 iFSHD ‡ Trevisan [17] 2008 ITA Case-series 5 7 iFSHD + 10-13Kb ‡ Lee…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the identification of non-FSHD signs in DRA carriers (category D) might serve as a proxy indicator of the co-presence of other genetic defects or modulators and requires additional studies and gene testing as indicated by the numerous cases reporting the association of FSHD with other neuromuscular conditions reviewed by Refs. [35][36][37][38][39][40][41][42][43][44][45][46][47]. Finally, asymptomatic/healthy carriers of 4-10 RU D4Z4 alleles, classified as Category C, stay asymptomatic/healthy in 79.1% of cases over the 5-year period.…”
Section: Discussionmentioning
confidence: 99%
“…30 Rarely, features resembling Mobius syndrome with ophthalmoplegia have been described. 31,32 Additional manifestations, such as retinal vasculopathy, 33 intellectual disability, epilepsy, 34 and cochlear dysfunction, 35 are more common among individuals with early-onset FSHD and large D4Z4 deletions. On occasion, these extramuscular features may be the initial presenting complaints, and thus, are particularly noteworthy for pediatric neurologists as potentially early signs of FSHD.…”
Section: Early-onset Fshdmentioning
confidence: 99%